Principles of granting compensation bonuses – substantive, legal and procedural issues - Małgorzata Ofiarska (Prawo Budżetowe Państwa i Samorządu)
This article presents a status, functions and principles of granting and transferring compensation bonuses from the Thermomodernization and Renovation Fund. The Fund is supplied mainly with subsidies from the state budget. They are a form of a non-repayable support for investors who carry out renovations in multi-family or single-family residential buildings, respectively. Only natural persons who are owners or co-owners of buildings with a so-called “council flats” are entitled to compensation bonuses. Compensation bonuses are a form of co-financing of expenses incurred by investors for performance of renovation projects and, at the same time, compensation for losses incurred by them during the period of an application of statutory limitations which determined rents. Thermomodernization and Renovation Fund is administered by Bank Gospodarstwa Krajowego. In this way, the legislator created a mechanism of a non-repayable financial support for investors from public funds, but with the use of bank methods of assessing applications submitted for granting compensation bonuses. The study positively verified the thesis about a need to use such support for investors who, in order to improve their functionality, bear costs of a renovation of residential buildings with council flats. It has been shown that the bonus is deliberate, i.e. it is granted in connection with the implementation of a specific project by the owner or co-owner of the building.